Role of serum estradiol and C-telopeptide on musculoskeletal pain in menopausal women - Siregar, Muhammad FG.; Terauchi, Masakazu; Lumbantobing, Jonathan T.; Pasaribu, Hotma P.; Prabudi, Muhammad O.; Ardiansyah, Edy; Effendi, Iman H.; Tobing, Immanuel DL.; Azmeila, Selly; Nabila, Nabila (Narra Sains Indonesia, 2024)
Musculoskeletal pain is one of the common symptoms of menopause syndrome throughout the world. Estradiol is the most potent and abundant derivative of estrogen and is associated with musculoskeletal pain, stiffness, and depressed mood during the menopausal transition. C-telopeptide is a molecule released during osteoclastic bone resorption and degradation of type I collagen, which is reported to have higher levels in individuals with musculoskeletal pain. An observational analytical study with a cross-sectional design was used in this research. Estradiol and C-telopeptide levels were measured in this study using enzyme-linked immunosorbent assay (ELISA). Musculoskeletal pain was assessed using the Nordic Musculoskeletal Questionnaire (NMQ) and the Menopause Quality of Life Questionnaire (MENQOL). Musculoskeletal pain was determined if the participant answered “yes” on questions number 12, 14 and 25 on the MENQOL. Data analysis was performed using the independent Student t-test for normally distributed data and the Mann-Whitney test for non-normally distributed data. A correlation test was performed using the Pearson correlation test for normally distributed data and the Spearman correlation test for non-normally distributed data. The results showed a non-significant relationship between estradiol and C-telopeptide levels with musculoskeletal pain assessed using the NMQ or MENQOL questionnaires. The correlation test also showed no correlation between estradiol and C-telopeptide levels in women with and without musculoskeletal pain.